Expanding the molecular signatures of malignant ossifying fibromyxoid tumours with two novel gene fusions: PHF1:FOXR1 and PHF1:FOXR2. Issue 6 (6th February 2023) - Srivastava, Pooja; Zilla, Megan L; Naous, Rana; Marker, Daniel; Khoshnoodi, Pooria; Burgess, Melissa; Herradura, Armando; Wu, Jinhua; Surrey, Lea F; John, Ivy
Abstract : Aims: Ossifying fibromyxoid tumor (OFMT) is a rare enigmatic tumor of uncertain differentiation that can be classified as typical, atypical, and malignant subtypes based on cellularity, nuclear grade, and mitotic activity. The majority of OFMTs, regardless of the risk of malignancy, harbor genetic translocations. We report two malignant OFMTs, including one with evidence of dedifferentiation, with novel genefusions. Methods and Results: Case 1 was a 63‐year‐old male with a dedifferentiated OFMT arising in the right wrist, while case 2 was a 41‐year‐old male with a malignant OFMT presenting as a posterior mediastinal mass. Case 2 showed multifocal expression with EMA and synaptophysin, while desmin and S100 were absent in both tumors. NGS sequencing studies detected PHF1::FOXR1 and PHF1::FOXR2 gene fusions in cases 1 and 2, respectively. Despite aggressive regimens, both progressed with wide spread metastases resulting in death within six years of diagnosis. Conclusions: We expand the genetic spectrum of OFMTs with two novel gene fusions, PHF1::FOXR1 and PHF1::FOXR2 . These cases confirm the previously reported tendencies for OFMTs with rare variant fusions to demonstrate malignant behavior, unusual morphology, and non‐specific immunophenotype.